Cardiac Transplantation in a Pediatric Patient with Systemic Sclerosis. (31st July 2011) - Johnson, Jonathan N.; Kvistad, Bonnie S.; Reed, Ann M.; Porter, Co‐burn J.; O'Leary, Patrick W.; Driscoll, David J.
ABSTRACT Introduction. Diffuse cutaneous systemic sclerosis (SSc) is rare in children, but has a poor prognosis when cardiomyopathy is present. Methods. We reviewed the case of a 14‐year‐old female with progressive skin thickening/tightness and dyspnea on exertion who was diagnosed with SSc. Results. Our patient was found to have severe restrictive cardiomyopathy with poor left ventricular systolic function (ejection fraction = 20%), unresponsive to the immunosuppression used to treat her SSc. There was no evidence of pulmonary fibrosis. The patient underwent orthotopic cardiac transplantation, with improvement in systemic symptoms. Two years after transplantation, she had elevated filling pressures during a surveillance catheterization, with no evidence of cellular rejection or coronary artery vasculopathy. Four months later, she developed severe ventricular dysfunction and dyspnea, despite a negative biopsy and negative C4d immunofluorescence staining. Her immunosuppression was intensified with improvement of cardiac function. Despite this, 1 month later she had sudden pulseless cardiac arrest from which she could not be revived. The family declined an autopsy. Discussion. We report a 14‐year‐old female with SSc who had cardiac transplantation. The etiology behind her recurrent restrictive physiology, cardiac dysfunction, and subsequent cardiac arrest remains unclear.